Linker histone H1.2 directs genome-wide chromatin association of the retinoblastoma tumor suppressor protein and facilitates its function - Munro, S; Hookway, E; Floderer, M; Carr, S; Konietzny, R; Kessler, B; Oppermann, U; La Thangue, N (Elsevier, 2017)
The retinoblastoma tumor suppressor protein pRb is a master regulator of cellular proliferation, principally through interaction with E2F and regulation of E2F target genes. Here, we describe the H1.2 linker histone as a major pRb interaction partner. We establish that H1.2 and pRb are found in a chromatin-bound complex on diverse E2F target genes. Interrogating the global influence of H1.2 on the genome-wide distribution of pRb indicated that the E2F target genes affected by H1.2 are functionally linked to cell-cycle control, consistent with the ability of H1.2 to hinder cell proliferation and the elevated levels of chromatin-bound H1-pRb complex, which occur in growth-arrested cells. Our results define a network of E2F target genes as susceptible to the regulatory influence of H1.2, where H1.2 augments global association of pRb with chromatin, enhances transcriptional repression by pRb, and facilitates pRb-dependent cell-cycle arrest.